2008
DOI: 10.1080/13691050701877526
|View full text |Cite
|
Sign up to set email alerts
|

Religion and spirituality among bisexual Black men in the USA

Abstract: Traditionally, religion has been a major source of institutional support and well-being for Black people in the USA. However, when juxtaposed against sexuality, religion's positive effect upon the lives of non-heterosexual individuals is questionable. Research suggests that non-heterosexuals often abandon structured religion for spirituality due to the homonegativity perpetuated through religious institutions. Although studies have examined religion and spirituality among gays and lesbians, few have examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 38 publications
4
94
1
Order By: Relevance
“…This is congruent with the documented positive relationship between spirituality and better Age, Spiritual Well-Being and Homonegativity 19 psychological health among LGB persons, such as decreased depression and internalized homophobia (Tan, 2005). One interpretation of these results would be that the search for meaning and purpose could constitute a coping strategy, in response to social stigma and discrimination (as identified in other studies, such as Jeffries et al, 2008).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…This is congruent with the documented positive relationship between spirituality and better Age, Spiritual Well-Being and Homonegativity 19 psychological health among LGB persons, such as decreased depression and internalized homophobia (Tan, 2005). One interpretation of these results would be that the search for meaning and purpose could constitute a coping strategy, in response to social stigma and discrimination (as identified in other studies, such as Jeffries et al, 2008).…”
Section: Discussionsupporting
confidence: 75%
“…Contrary to common belief, research shows that LGB persons are not devoid of religiosity and spirituality (Tan, 2005;García, Gray-Stanley & Ramirez-Valles, 2007;Ridge, Williams, Anderson & Elford, 2007;Jeffries, Dodge & Sandfort, 2008;Cutts & Parks, 2009;Halkitis et al, 2009). Nonetheless, there are specific stressors that LGB persons face in their religious communities (Jeffries et al, 2008) that can, at times, potentially undermine their well-being (Coyle & Rafalin, 2000;Gage Davidson, 2000;Ridge et al, 2007).…”
Section: Lesbian Gay and Bisexual People Religion And Spiritualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Ward (2005) describes Black churches as "a significant source of the homophobia that pervades black communities" (p. 493), and argues that this theologically-based homophobia can adversely impact self-esteem, social relations and health among LGBT African Americans. Given that religion constitutes a generally important aspect in the lives of many African Americans (Battle & Defreece, 2014;Walker & Langmire, 2013), it has been shown that LGBT African Americans seek to construct coherence between their religious and sexual identities by inter alia challenging the moral authority of the Black Church (Pitt, 2010), deriving a sense of belonging in particular domains of the church such as music ministry (Jeffries et al, 2008) and immersing themselves in more gay friendly sections of the Black Church (Chaney & Patrick, 2010). Moreover, a key theme in research into the social relationships of LGBT African Americans has been that of racism, which is said to impede social capital and integration in the wider LGBT community.…”
Section: Ethnic and Religious Minority Gay Menmentioning
confidence: 99%